ASSESSMENT OF MOVEMENT-INDUCED TIME-VARYING MAGNETIC FIELDS EXPOSURE IN MAGNETIC RESONANCE IMAGING BY A COMMERCIAL PORTABLE MAGNETOMETER. Issue 3 (26th February 2019) - Filice, Silvano; Rossi, Raffaella; Crisi, Girolamo
Abstract: The purpose of this study was to describe a simple procedure to assess head exposure of MRI workers to time-varying magnetic field, due to their movements in the static magnetic field of a 3T MRI scanner. A group of MRI workers were provided with a commercial portable meter that stored in its internal memory the instantaneous B values. The dB/dt was obtained by the post hoc processing of measured data. The movement-induced time-varying electric field (TVEF) was calculated from dB/dt. The weighted peak index was evaluated in the frequency domain, by first computing the spectrum of dB/dt waveform, to verify the compliance with the exposure limits. The portable magnetometer may be useful to locally explore the MRI workers exposure to time-varying magnetic field and perform the local risk assessments in order to carry out the obligations laid down by Directive 2013/35/EU.